Etiology and prognosis of encephalitis in French Guianese children: a retrospective record-based study. Issue 7 (July 2020) - Elenga, Narcisse; Roux, Alexandre; Cuadro-Alvarez, Emma; Martin, Elise; Kallel, Hatem; Defo, Antoine
Abstract: Acute encephalitis is an important cause of mortality and morbidity in children. We retrospectively identified children (≤15 years of age) admitted with suspected encephalitis at the Intensive Care Unit of the Pediatric Department of Cayenne Hospital between January 2007 and December 2018. A total of 30 children with acute encephalitis were identified. The incidence rate varied from 0 to 10.40 cases/100000 children under 15 years. Proven encephalitis was diagnosed in 73% of patients. Nine cases of acute disseminated encephalomyelitis were diagnosed. The causes of infection (44%) were Haemophilus influenza e, followed by Cryptococcus spp and Varicella Zoster Virus. Four children (13%) died: one case of Streptococcus pneumoniae, one of Haemophilus influenzae, one of Mycobacterium tuberculosis and one with no identified cause. Seventeen percent of children had moderate to severe neurological sequelae. The only factor associated with poor outcome was young age at the time of hospitalization (p = 0.03). Conclusion: This study highlights both vaccine-preventable pathogens and acute disseminated encephalomyelitis as the leading causes of childhood encephalitis in French Guiana.